Uji Kesukaan Kimchi dengan Modifikasi Asinan Buah - Roy Daniel Samboh; Evelyn Sazcipta Mekarningtyas (Eduturisma, 2024)
Abstract This research was conducted because the researcher wanted to create kimchi innovation with local fruits in Indonesia, where fruits are horticultural products or easily perishable, so there needs to be an effort to extend the shelf life of fruits and increase their selling price. Therefore, the author was interested in creating kimchi innovation with fruit pickle modification. The research method and data collection techniques used were (1) Experimental Method (2) Literature Study (3) Questionnaire. From the results of the research using organoleptic tests that have been conducted, it can be concluded that kimchi with fruit pickle substitution with the best mean result (3.95) was found in the characteristic color of fruit kimchi, which has various colors from the fruit and a deep red color from the kimchi substitution spices. Key Words : Organoleptic Test, Modification, Kimchi, Pickled Fruit